2017
DOI: 10.1038/onc.2016.470
|View full text |Cite
|
Sign up to set email alerts
|

MLL-ENL-mediated leukemia initiation at the interface of lymphoid commitment

Abstract: Translocations involving the mixed lineage leukemia-1 are recurrent events in acute leukemia and associate with lymphoid (ALL), myeloid (AML) or mixed lineage (MLL) subtypes. Despite an association with ALL in humans, murine MLL fusion models are persistently restricted to AML. We here explored this issue using an inducible mixed lineage leukemia-eleven nineteen leukemia (MLL-ENL) mouse model. Although multiple progenitor cell types with myeloid potential are potent AML leukemia-initiating cells, also the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Kotrova et al, have demonstrated in ambiguous lineage leukemia with distinct T and M-blast populations the presence of typical T-ALL mutations that activate the NOTCH1 signaling pathway 27. In mice, aberrations such as KMT2A-ENL and KRASG12D cooperate to the rise of both AML and T-ALL 28. We have found one T/M-MPAL case with KMT2A-ENL, KRAS and NOTCH1 mutation that may be more consistent with Ugale’s animal model 28…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Kotrova et al, have demonstrated in ambiguous lineage leukemia with distinct T and M-blast populations the presence of typical T-ALL mutations that activate the NOTCH1 signaling pathway 27. In mice, aberrations such as KMT2A-ENL and KRASG12D cooperate to the rise of both AML and T-ALL 28. We have found one T/M-MPAL case with KMT2A-ENL, KRAS and NOTCH1 mutation that may be more consistent with Ugale’s animal model 28…”
Section: Discussionsupporting
confidence: 78%
“…In mice, aberrations such as KMT2A-ENL and KRASG12D cooperate to the rise of both AML and T-ALL 28. We have found one T/M-MPAL case with KMT2A-ENL, KRAS and NOTCH1 mutation that may be more consistent with Ugale’s animal model 28…”
Section: Discussionsupporting
confidence: 73%
“…35 In addition, unlike the Mll-Enl translocator model, 32 this DOX-inducible MLL-ENL produced only AML when expressed in T-cell progenitors. 51 More surprisingly, when they subfractionated the LSK compartment into granulocyte-monocyte-lymphoid progenitors, multipotent progenitors, and CD150 1 CD48 2 HSCs, only granulocyte-monocyte-lymphoid progenitors produced a transplantable AML. 50 MLL-ENL expressing HSCs not only failed to induce AML, they also displayed severely compromised reconstitution potential.…”
Section: Modeling Mll-enl Leukemias In Micementioning
confidence: 99%
“…Erythrocytes were sedimented with 1% dextran T500 (Sigma-Aldrich) and remaining erythrocytes were lysed with ACK (0.15 M NH 4 Cl, 10 mM KHCO 3 , and 0.1 mM EDTA; pH 7.2–7.4). The cells were stained and analyzed as described ( Ugale et al, 2017 ). The absolute lymphocyte counts were determined by multiplying the total white blood cell counts and the frequencies of B or T cells established by the FACS analysis.…”
Section: Methodsmentioning
confidence: 99%